A Comprehensive Review of the Cognitive Determinants of Anxiety and Rumination in Social Anxiety Disorder. Issue 3 (25th October 2016) - Modini, Matthew; Abbott, Maree J.
Abstract : Social anxiety disorder (SAD) is characterised by an intense fear of social situations in which the individual believes they may be negatively evaluated (American Psychiatric Association, 2013). A number of cognitive models (Clark & Wells, 1995 ; Hofmann, 2007 ; Rapee & Heimberg, 1997 ) have been proposed that provide frameworks for understanding the key cognitive processes involved in SAD. Negative rumination, which can be divided into pre- and post-event rumination, appears to be a key maintaining factor in the cycle of social anxiety. However, there are mixed findings regarding the cognitive predictors of post-event rumination and a lack of research regarding the consequences and predictors of pre-event rumination. Furthermore, there has been little empirical research investigating the effects of targeting negative rumination and state anxiety in social anxiety treatment. If the cognitive predictors of negative rumination can be determined then they can be targeted when designing interventions that aim to break the vicious cycle of social anxiety. The state of research investigating the cognitive determinants of state anxiety and negative rumination is reviewed and suggestions are made for continuing research.